2022
DOI: 10.21203/rs.3.rs-1527814/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrical Programmable Low-loss high cyclable Nonvolatile Photonic Random-Access Memory

Abstract: The retention-of-state functionality provided by memories is fundamental to any Turing machine and neural network, hence is critical for any information system today. While emerging optical machine learning accelerators and photonic neuromorphic computing paradigms provide promising signal processing and computing performance, the lack of a photon-photon force in the universe makes storing optical information challenging. Fortunately, phase change materials provide such a missing memristive nonvolatile functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…47−50 However, we note that the choice of GST is preferred for compatibility with existing high-volume manufacturing because this material has been extensively studied in electronic memories and is technologically mature. 17,51 Although our 2 × 2 programmable unit displayed the highest reported cyclability among electrically controlled PCM-based photonic devices (we note a work came out during the review of this study shows half million cycles operations using a tungsten heater 52 ), it is still significantly lower than the records obtained for electronic memories (∼10 12 cycles, potentially scale up to 10 15 cycles). 17,51 The cyclability of our device is mainly limited by thermal reflowing and material ablation because of the large GST volume (Supplementary, Section S7).…”
Section: ■ Discussionmentioning
confidence: 65%
“…47−50 However, we note that the choice of GST is preferred for compatibility with existing high-volume manufacturing because this material has been extensively studied in electronic memories and is technologically mature. 17,51 Although our 2 × 2 programmable unit displayed the highest reported cyclability among electrically controlled PCM-based photonic devices (we note a work came out during the review of this study shows half million cycles operations using a tungsten heater 52 ), it is still significantly lower than the records obtained for electronic memories (∼10 12 cycles, potentially scale up to 10 15 cycles). 17,51 The cyclability of our device is mainly limited by thermal reflowing and material ablation because of the large GST volume (Supplementary, Section S7).…”
Section: ■ Discussionmentioning
confidence: 65%
“…Early works reported limited cyclability (around 10 cycles) 84 and low optical contrast (less than 1 dB). 82 Recently, high endurance (over half a million cycles 85 ) and large contrast switching (more than 10 dB contrast) have been achieved using external heaters 45,83,85,86 with high-quality encapsulation.…”
Section: Photonicsmentioning
confidence: 99%
“…There are predominantly two types of electrical heaters: (1) doped intrinsic semiconductor, such as silicon, on which the PICs are fabricated; 45,83,87 and (2) extrinsic heaters, such as metal, 85 graphene, 88,89 indium-doped tin oxide (ITO), 84,86 or fluorine-doped tin oxide (FTO). 90 A detailed simulation study of different heaters revealed that graphene heaters are much more electrical energy-efficient than doped semiconductors (such as PIN diode-based silicon heaters) or ITO heaters, 91 primarily because of graphene's much smaller active volume.…”
Section: Photonicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrum plotted indicates that the absorption is 8 dB, which implies a 0.08 dB/µm absorption coefficient of the GSSe onchip. Significantly, the imaginary part of the effective refractive index in the amorphous state is 2.18 × 10 −5 , leading to an exceedingly small unit of passive insertion loss (16).…”
Section: Phase Change Materials For Tunable Componentmentioning
confidence: 99%